Fish farming systems diversity and implications in the Republic of Benin: Fish farm types and their economic performance - Adegbola, Patrice Ygue; Crinot, Geraud Fabrice; Arouna, Aminou (Wiley, 2022)
Fish farming is promoted in the Republic of Benin to meet the demands of fish con sumption and increase exports to neighbouring countries. Targeting fish farm policy interventions to increase the efficiency of heterogeneous fish farming systems is a challenge. Farm type delineation allows for simplifying the diversity in fish farming systems. Multivariate statistical techniques combined with the Calinski and Harabasz pseudo F statistic and bootstrapping were applied to determine the realistic num ber of fish farm types. Four fish farm types were identified and characterised based on farm intensity, species diversification, and the management capacity of operators. Furthermore, profits and both labour and capital productivity increased continuously from the extensive fish farms to the semi-intensive farms. They also vary widely within farm types across the country. These farm types may be supported by appropriate fish farming promotion policy interventions. Most importantly, training programs must be tailored to each farm type to strengthen the technical and managerial capacity of the fish farmers. KEYWORDS bootstrap, Calinski and Harabasz pseudo F statistic, cluster analysis, fish farm typology, Jaccard coefficient, typology stability